Structure-Activity and Lipophilicity Relationships of Selected Antibacterial Natural Flavones and Flavanones of Chilean Flora - Urzua-Moll, A; Wilkens-Anwandter, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
In this study, we tested eight naturally-occurring flavonoids - three flavanones and five flavones - for their possible antibacterial properties against four Gram-positive and four Gram-negative bacteria. Flavonoids are known for their antimicrobial properties, and due their structural diversity; these plant-derived compounds are a good model to study potential novel antibacterial mechanisms. The lipophilicity and the interaction of antibacterial compounds with the cell membrane define the success or failure to access its target. Therefore, through the determination of partition coefficients in a non-polar/aqueous phase, lipophilicity estimation and the quantification of the antibacterial activity of different flavonoids, flavanones, and flavones, a relationship between these parameters was assessed. Active flavonoids presented diffusion coefficients between 9.4 × 10-10 and 12.3 × 10-10 m2/s and lipophilicity range between 2.0 to 3.3. Active flavonoids against Gram-negative bacteria showed a narrower range of lipophilicity values, compared to active flavonoids against Gram-positive bacteria, which showed a wide range of lipophilicity and cell lysis. Galangin was the most active flavonoid, whose structural features are the presence of two hydroxyl groups located strategically on ring A and the absence of polar groups on ring B. Methylation of one hydroxyl group decreases the activity in 3-O-methylgalangin, and methylation of both hydroxyl groups caused inactivation, as shown for 3,7-O-dimethylgalangin. In conclusion, the amphipathic features of flavonoids play a crucial role in the antibacterial activity. In these compounds, hydrophilic and hydrophobic moieties must be present and could be predicted by lipophilicity analysis. © 2017 by the authors. Licensee MDPI.
Keywords: antibacterial flavonoids; structure-activity relationship; lipophilicity